Effluent and serum protein N-glycosylation is associated with inflammation and peritoneal membrane transport characteristics in peritoneal dialysis patients - Evelina Ferrantelli (Nature Portfolio, 2018)
Abstract Mass spectrometric glycomics was used as an innovative approach to identify biomarkers in serum and dialysate samples from peritoneal dialysis (PD) patients. PD is a life-saving treatment worldwide applied in more than 100,000 patients suffering from chronic kidney disease. PD treatment uses the peritoneum as a natural membrane to exchange waste products from blood to a glucose-based solution. Daily exposure of the peritoneal membrane to these solutions may cause complications such as peritonitis, fibrosis and inflammation which, in the long term, lead to the failure of the treatment. It has been shown in the last years that protein N-glycosylation is related to inflammatory and fibrotic processes. Here, by using a recently developed MALDI-TOF-MS method with linkage-specific sialic acid derivatisation, we showed that alpha2,6-sialylation, especially in triantennary N-glycans from peritoneal effluents, is associated with critical clinical outcomes in a prospective cohort of 94 PD patients. Moreover, we found an association between the levels of presumably immunoglobulin-G-related glycans as well as galactosylation of diantennary glycans with PD-related complications such as peritonitis and loss of peritoneal mesothelial cell mass. The observed glycomic changes point to changes in protein abundance and protein-specific glycosylation, representing candidate functional biomarkers of PD and associated complications.